Takhrij Hadits Nilai Kemanusiaan (Berbuat Baik kepada Istri dan Orang lain) - Imam syafii (Universitas Yudharta Pasuruan, 2021)
Abstract Doing good toward human beings is something that must be done as social beings in order to create a peaceful life in society. Being a very important thing to do good to the wife, this is often neglected by husbands. Doing good to the wife is an absolute obligation for the husband by doing good will create peace in the family and raise peace-loving generations. In this study, we will discuss the study of takhrij hadith about doing good to the wife and others, which will examine partially, namely how the reliability of the narrators, the connection of sanad, whether or not the hadith is valid, converts (note whether or not) the hadith is valid and examines the hadith in detail. Simultaneously, this study uses the Gamee Al-Kaleem application version 4.5. an application designed for Takhrij Al-Hadith.Based on the research’s finding, it is concluded that first, the narrator Sufyan Al Tsauri is a Tsiqah narrator. Second, the hadiths studied are in the Shohihul Al-isnad category. Third, this hadith about doing good to family and others can be concluded to be in the Sahih al-Matan category. Fourth, the existence of this hadith and other hadiths are in one corridor to support each other. Fifth, the hadith about doing good to family and other people under study does not contain illat which can make it rejected by the Aqli argument. Sixth, by partial research, this hadith is shohihul al-hadith/shohih lidzatihi. Seventh, the simultaneous research shows that this hadith is ahad ghorib.